Structural identification and osteogenic activity of a novel heteropolysaccharide obtained from female flowers of Humulus lupulus. Issue 2 (24th January 2019) - Chen, Xiaoxia; Hou, Xin; Qing, Degang; Zhang, Qian; Yan, Chunyan
Abstract : The flowers and infructescences of Humulus lupulus are used worldwide in beer brewing as an essential flavoring ingredient, and are also used in traditional Chinese medicine. Abstract : Humulus lupulus is distributed mainly in Asia, Europe, and North America, and the flowers and infructescences are used worldwide in beer brewing as an essential flavoring ingredient. In China, the main producing areas are the Xinjiang Uygur Autonomous Region and Gansu provinces. The annual production of H. lupulus in China accounts for about 13% of worldwide production, ranking third after the United States and Germany. The female flower of H. lupulus also is used in traditional Chinese medicine, but the bioactive components responsible for its benefits remain unclear. In this study, we isolated a homogeneous polysaccharide (HLP50-2) from female flowers of H. lupulus via DEAE-52 cellulose and Sephadex G-75 gel filtration chromatography. The molecular weight was 73.25 kDa. Chemical methods, gas chromatography-mass spectrometry, and nuclear magnetic resonance analyses showed that HLP50-2 consisted of →4)-β-d -GlcA p -(1→, →4)-α-l -Rha p -(1→, →5)-α-l -Ara f -(1→, α-l -Ara f -(1→, →3, 6)-β-d -Gal p -(1→, α-d -Gal p -(1→, →3, 4, 6)-β-d -Gal p -(1→, β-d -Xyl p -(1→, →6)-α-d -Gal p -(1→, and →4)-β-d -Gal p -(1→. Advanced structural analysis indicated that HLP50-2 has a sheet-like structure with uneven distribution and the surface was smooth. In addition, we used MC3T3-E1 cells to evaluate the osteogenic activity of HLP50-2. The results show that HLP50-2 significantly promoted the proliferation, differentiation, and mineralization of MC3T3-E1 cells at concentrations of 12.5 μg mL −1 and 25 μg mL −1 . In particular, at 25 μg mL −1, the promoting mineralization effect of HLP50-2 was better than that of the positive control, 17β-estradiol, and the alkaline phosphatase activity after 10 d of treatment was comparable to that of the positive control. The extraction, isolation, purification, structural identification, and osteogenic activity of H. lupulus polysaccharides suggest that homogeneous polysaccharide HLP50-2 has pronounced anti-osteoporosis activity. Therefore, it has broad application prospects in pharmaceutical industries and health-care products.